The legislature and the constituency projects in Nigeria - Yusuf, Yusuf Abdu; Yusoff, Kamarul Zaman; Zengeni, Knocks Tapiwa (Society of Scientific Research and Education (SSRE), 2018)
This study represents the idea of constituency projects and examines the role of the legislature in that regards in Nigeria. The central argument is that doubt has been raised regarding the execution of constituency projects and its constitutional status in the country, moreover, its implementation is marred by misconception and mismanagement. The paper used interview method to generate required information and interpretive approach in its analysis.The paper contends that ordinarily, the idea of constituency projects should not arise in presidential democracy, however, since the electorates desire projects from their lawmakers the idea could be used to bring developmental projects to the constituencies.Furthermore, the study reveals that funding and implementation of these projects is the responsibility of the executive, the legislature only design and selects its locations. It recommended that since constituency projects are expedient it should have a constitutional basis.